The Effect of Adding Spent Mushroom, Biofertilizers and Mineral Fertilizers on the Availability of Some Nutrients And The Soil Aggregates Stability - Hudah T. Al-Hrkane; Iman Q. Mohammed; Luma S. J. Al-Taweel (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
This field experiment was carried out to study the Spent Mushroom farm wastes, biological and mineral fertilizers and their effect on the availability of soil nutrients and soil aggregate in a field planted with Zea mays L. measurements were taken at two-time intervals (45 and 110 days after planting). The results of the experiment showed that the use of Spent Mushroom and the application of biological and mineral fertilizers at different levels a significant increase in soil nutrient availability and soil aggregate stability for all time periods. The highest average was 50.03 mg N kg-1 soil for the treatment (O1B1M3) at 45 days of Planting, 25.27 mg P kg-1 soil at 45 days of Planting for the treatment (O1B1M3), 258.3 mg K kg-1 soil for the treatment (O1B1M3) at 45 days of Planting and 5.77 mg Zn kg -1 soil at harvest for the treatment (O1B2M2). And the soil aggregate was 25.99% at harvest for the treatment (O1B1M2) compared to the controltreatment (26.88 mg N kg-1 soil, 7.74 mg P kg-1 soil, 186 mg K kg-1 soil, 2.59 mg Zn kg-1 soil and 13.47%).  despite the varying results of the fertilizers used from the above that the use of Spent Mushroom farm waste as Organic fertilizer, and both types of biological and mineral fertilizers levels led to improve the availability of soil nutrients, which is reflected in the fertility and health of the soil, Through, the availability of Nutrients (nitrogen, phosphorus, potassium, and zinc) and Soil aggregates in soil as indicators of soil health